Rekonstruksi Ijab dan Kabul dalam Transaksi Ekonomi Berbasis Online - Ridwan, Ridwan (Al-Manahij: Jurnal Kajian Hukum Islam, 2017)
In Islamic law, the position of incentives in the economic transaction becomes a determinant factor for the validity of a contract. The technical and consent in the formulation of classical jurisprudence is done physically, marked by a meeting between the parties involved in a contract site. The communication technology revolution has spawned an online-based transaction model that is e-commerce, or e-marketing, through internet technology tools where the parties involved do not meet physically and the contract object cannot be handed over directly. This reality illustrates the existence of gap in the Islamic law theory with an empirical practice that requires a legal answer. This article proves that online-based economic transactions are legitimate contracts in the view of Islamic law based on legal analogy argument, i.e.to equate an online contract with an orderpurchase contract. The construction of consent in an online-based contract must be based on certain norms, namely clarity of specification of goods, means of payment and technicality, technical delivery of goods, terms of the contract cancellation and terms of dispute. These detailed and rigorous rules are an illustration of the importance of caution in conducting online transactions to avoid losses by adhering to the sadd al-zari>’ah method in order to close the possibility of emerging harmful.